Ungentle goodnights : life in a home for elderly and disabled naval sailors and Marines and the perilous seafaring careers that brought them there - McKee, Christopher, 1935- (Naval Institute Press, 2018)
"Ungentle Goodnights uses the records of the United States Naval Asylum (later the United States Naval Home), a residence for disabled and elderly sailors and Marines established by the U.S. government, to recover the lives of the 541 men who were admitted there as lifetime residents between 1831 and 1866. The records of the Naval Asylum are an especially rich source for discovering these lower-deck lives because would-be residents were required to submit summaries of their naval careers as part of the admission process. Using these and related records, published and manuscript, it is possible to reconstruct the veterans' lives from their teenage years (and sometimes earlier) until their deaths."--Provided by publisher.